Mechanical characterization of epoxy-HA hybrid composites reinforced with woven carbon fiber and nylon fiber mesh for external fixator - Harini Sosiati; Ankas Pamasti; Rahmad Kuncoro Adi; Aulia Zaki Kusuma; Putra Dwi Darmawan; Totok Suwanda (Materials Research Express, 2025)
Biomedical composites have been widely developed using polymer materials due to their adjustable lightweight and mechanical properties through constituent variations. This study investigates hybrid laminated composites reinforced with woven carbon fiber (C) and nylon mesh fiber (N) in an epoxy (E) matrix containing hydroxyapatite (HA) microparticles (200 mesh). Four different layering sequences (C-N-C-N-C, C-N-N-C-C, N-C-N-C-C, and N-N-C-C-C) were tested to evaluate their mechanical performance for potential application in external fixators. Composites were fabricated using a hand-laying-up process followed by hot press molding, with a reinforcement ratio of 20 vol% (C+N) to 80 vol% (79 vol% E + 1 vol% HA). Prior to fabrication, C was pre-treated in liquid nitrogen (N _2 ) for 10 min. Mechanical testing, including tensile, bending, impact, and hardness tests, revealed that all composite types exhibited higher mechanical strength than human cortical bone, while their Young’s moduli remained within the cortical bone range. Among the tested variations, the C-N-N-C-C composite demonstrated the highest tensile strength (205 MPa) and Young’s modulus (12.85 GPa). Additionally, it exhibited the highest flexural strength (137.95 MPa), impact strength (89.19 kJ m ^−12 ), and hardness (69.33 Shore-D). Finite element analysis using ANSYS Workbench 2019 R3 further confirmed its suitability, with a von Mises stress of 17.35 MPa. Based on these findings, the C-N-N-C-C composite is recommended as a viable material for external fixators, particularly for individuals aged 25 to 40 years.